The values of citizenship and its relation to the responsibility of the employees of the Ministry of Defense - Jarjis Younes, Yasmine; Faleh, Naglaa (Al-Adab Journal, 2019)
Citizenship in its general sense is the sense of belonging to the group and sharing its feelings. In the case of alienation, it means nostalgia for the homeland, which reminds man of the customs, traditions and behavior of its citizens, as well as the citizen to interact in the widest sense with the homeland and with the citizens. "In terms of" land "geographical, historical, social and political, so citizenship and the national spirit is the real engine of social life, and that national spirit includes a set of values ​​that determine the relationship of the individual community And in the same sense that responsibility in its general sense is the recognition of the individual's actions and the willingness to bear the consequences of these acts, the ability to blame the individual himself first, and the ability to meet after that Through its own efforts and free administration, and is responsible for freedom research goals Current search targets:1. Building a scale of citizenship values ​​among employees of the Ministry of Defense.2. Measuring the values ​​of citizenship among the employees of the Ministry of Defense.3. Measuring the sense of responsibility among employees of the Ministry of Defense.4. Know the nature of the relationship between the values ​​of citizenship and the sense of responsibility among employees of the Ministry of Defense. The researchers identified the terms in the current research as follows:The results of the research that the employees of the Ministry of Defense have the values ​​of loyalty and belonging and love of the homeland and the defense and self-esteem because it represents their identity and their entity, which preserves the dignity of the human being and this is the result of their sense of responsibility towards their country and the values ​​of citizenship and its relationship positively with a sense of responsibility.